1975
DOI: 10.1029/rg013i002p00383
|View full text |Cite
|
Sign up to set email alerts
|

Gabbro‐eclogite reaction rate and its geophysical significance

Abstract: The gabbro-garnet granulite-eclogite transformation may play a significant role in driving the motions of terrestrial lithospheric plates. Whether or not this transformation is in fact important as a driving mechanism for plate tectonics depends on the relationship of the reaction time to geologic time. Solid state diffusion under completely dry conditions is investigated as a possible model for the gabbro-eclogite reaction, with the result that it could not produce the transition in geologically meaningful ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(81 citation statements)
references
References 64 publications
2
79
0
Order By: Relevance
“…In order to extrapolate experimental kinetic data to geological conditions, the effects of variables such as temperature, pressure, grain size, and the catalytic role of water must be understood. The effectiveness of water as a catalyst is qualitatively well known, and is so pronounced that the availability of water, rather than temperature, has been suggested, for example, as the most important factor controlling the rate of the gabbro to eclogite transformation during subduction (Ahrens and Schubert, 1975). However, apart from preliminary investigations of the quartz + periclase ~ forsterite reaction (Fyfe et al, 1958, pp.…”
Section: Water As a Catalyst In Mineral Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to extrapolate experimental kinetic data to geological conditions, the effects of variables such as temperature, pressure, grain size, and the catalytic role of water must be understood. The effectiveness of water as a catalyst is qualitatively well known, and is so pronounced that the availability of water, rather than temperature, has been suggested, for example, as the most important factor controlling the rate of the gabbro to eclogite transformation during subduction (Ahrens and Schubert, 1975). However, apart from preliminary investigations of the quartz + periclase ~ forsterite reaction (Fyfe et al, 1958, pp.…”
Section: Water As a Catalyst In Mineral Reactionsmentioning
confidence: 99%
“…Although it is often assumed that this value is applicable to diffusion of ions through thin aqueous films in intergranular regions (e.g. Ahrens and Schubert, 1975;Walther and Wood, 1984), Rutter (1976) has suggested that the diffusivity of ions in thin films is reduced by about five orders of magnitude relative to the diffusivity in a bulk fluid. The basis of this estimate is first the inverse relation between diffusivity and fluid viscosity, the StokesEinstein equation…”
Section: Diffi4sion In Fluid Filmsmentioning
confidence: 99%
“…For the lowermost section of thick igneous crust, there is a possibility of garnet growth [Ringwood and Green, 1964;Ringwood and Green, 1966]. For anhydrous igneous rocks with a typical cooling history, however, this garnet growth is unlikely because of kinetic barriers to reaction [Ahrens and Schubert, 1975]. Even if garnet forms, the velocity and density of resultant garnet granulites and eclogitic rocks both increase following Birch's law [e.g., Sobolev and Babeyko, 1994].…”
Section: The Paradox Of the Margin Gravity Highmentioning
confidence: 99%
“…The release of H 2 O from the serpentine in the mantle would cause H 2 O saturation in the crust just above the dehydration zone, and might have resulted in the retardation of the dehydration reactions in the crust (see Ahrens and Schubert, 1975), reducing seismicity in the subducting crust. To discuss this effect more qualitatively, we have to know better the processes of aqueous fluid migration in the crust and mantle associated with dehydration-hydration reactions, which is beyond the scope of the present study.…”
Section: Slab Seismicity Beneath Kantomentioning
confidence: 99%